Aspects phytochimiques de l'Ephedra alata et ses effets sanitaires - REHOUMA Safa (Universty Of El-oued جامعة الوادي, 2018)
Ephedra is one of the medicinal plants used in traditional medicine to treat many diseases. The purpose of this study is to identify the secondary components and to evaluate the antibacterial activity of the aqueous extract of the plant Ephedra alata growing in the wild in Khenchela and analyze it. The present study is part of the contribution to the valorization of a medicinal plant. Ephedra alata has a great pharmacological importance in the world and is renowned for its resistance to drought. The extract obtained after maceration in distilled water gave a moderate yield of 16.38%. The phytochemical study showed the presence of various secondary metabolites in the aerial part of the plant such as polyphenols, flavonoids, tannins, alkaloids, saponosides, reducing sugars and terpenoids. With a high flavonoid content that reaches an average value of 11.423 μgEQ / mg. The disk diffusion method in agar medium, showed a strong activity of the extracts of the plant against the growth of S. enteric, and low inhibitory activity of the growth of P. aeruginosa. According to the ethnobotanical survey, the pharmacological importance of the plant seems to be ignored by a large part of the population, but some scientific researches in pharmacology show that Ephedra alata has a considerable therapeutic importance and can be used as remedies for various diseases.
master
Keywords: Ephedra alata; Antibacterial activity; Evaluation; Secondary metabolites; Health effects; Khenchela.